2018
DOI: 10.1111/nph.15394
|View full text |Cite
|
Sign up to set email alerts
|

Development of a method for protonema proliferation of peat moss (Sphagnum squarrosum) through regeneration analysis

Abstract: The moss Sphagnum (peat moss) is ecologically and economically important. There is a paucity of physiological and developmental studies on Sphagnum because of the lack of an axenic culture system for its whole life cycle. A culture system has been established for the Sphagnum gametophore, but not the protonema (juvenile vegetative stage after spore germination). Therefore, the aim of this study was to develop a protonema culture system for Sphagnum. Sphagnum squarrosum gametophore tissue was disrupted and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…To our knowledge, no genetic transformation of any Sphagnum species has been reported hitherto. Because protoplasts derived from protonemal cells are the preferred target for genetic transformation in P. patens , the report about protonema‐induction in S. squarrosum (Zhao et al ., 2019) paves the way for such experiments in the future.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…To our knowledge, no genetic transformation of any Sphagnum species has been reported hitherto. Because protoplasts derived from protonemal cells are the preferred target for genetic transformation in P. patens , the report about protonema‐induction in S. squarrosum (Zhao et al ., 2019) paves the way for such experiments in the future.…”
Section: Resultsmentioning
confidence: 96%
“…Initial results with this clone indicated that it can grow in a natural habitat without an intermediate hardening step (Decker & Reski, 2020). Another improvement is the establishment of a protonema‐proliferation protocol for Sphagnum squarrosum (Zhao et al ., 2019). Besides these two species, we found only one report of the establishment of S. fallax cultures in a bioreactor (Rudolph et al ., 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Bar = 3 mm. (E) Photo of a leaf with green and white cells in S. squarrosum (Li et al, 2019 ). Bar = 100 μm.…”
Section: Bryophytes' Morphology and Life Cyclementioning
confidence: 99%
“…Similar to other mosses in these regions, they appear to reproduce asexually through dispersal of vegetative propagules-small fragments of colonies (Skotnicki et al, 2002). Protonema proliferation plays an essential role in the asexual processes of differentiation and regeneration (Zhao et al, 2019). Since bryophytes commonly possess most key innovations of land plant evolution, the Antarctic psychrophilic mosses represent an emerging model system for studying responses and sensitivities to environmental changes (Convey and Peck, 2019).…”
Section: Introductionmentioning
confidence: 99%